DESINFORMATION AND DIGITAL ELEITORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
Introduction: One of the main challenges for democracy in the digital age is so-called Fake News, or disinformation. It occurs through the massive dissemination of false news and misleading content. This risk increases during electoral periods, impacting voters’ decision-making and threatening the integrity of the process. The problem intensified especially during the 2022 elections, reaching unprecedented proportions due to the advancement of technology and social media. Objective: To analyze the phenomenon of electoral disinformation, its impacts, and ways to combat it. Method: Qualitative literature review based on the analysis of case law from the Superior Electoral Court (TSE) and other studies collected via Google Scholar between 2020 and 2025. Results: Electoral disinformation campaigns in Brazil have intensified in recent years, with the 2018 elections as a turning point and reaching new heights in 2022. The narratives often aim to undermine trust in the electoral system and attack democratic institutions (such as the TSE and STF) and opposing candidates. Conclusion: According to the documents collected, disinformation directly affects democracy due to social wear and the attempt to divide the population. This requires continuous and coordinated efforts among the judiciary, digital platforms, civil society, and public agencies. Legislation must be constantly improved, with slander, defamation, and insult already considered crimes, while also seeking to increase transparency, promote media literacy, and better define the boundaries between freedom of expression and the spread of harmful false content.
Keywords: Disinformation.; Fake News.; Judiciary.